DESIGNING LECTORA INSPIRE – BASED MATRIX LEARNING MATERIAL FOR SENIOR HIGH SCHOOL STUDENT AT GRADE XI - Nurul Hamdinesha; Rosliana Siregar; Syahlan Syahlan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The government limits the social activities during the Covid-19 pandemic; as a result, the learning process was no longer carried out face-to-face. Therefore, an appropriate alternative was needed to facilitate the learning process. This study aimed to design a valid Lectora Inspire-based matrix learning materials for grade  XI high school students. This research was a part of development research utilizing 4D model by Thiagarajan. However, this study limited only on defining and designing stage. Defining and designing were conducted through a literature review followed by measuring the level of validation of Lectora Inspire-based learning materials. This research was conducted for three months, from July to October 2020. The instrument was the validation sheet given to 4 (four) material experts and 2 (two) media experts for Lectora Inspire-based learning materials. The results showed that the learning material developed based on Lectora Inspire had met the valid requirements. The results of observation from the validators towards the the materials and media showed a good score after the materials were revised as suggested by the validators. Lectora Inspire – based learning materials developed had many advantages compared to the learning materials created using other programming applications.